Socio-Economic Reflections of Increasing Tourist Mobility from Turkey to Greece: A Mixed-Method Sentiment Analysis on YouTube Comments (Third Sector Social Economic Review, 2025)
The main purpose of this study is to reveal the socio-economic dynamics underlying the increasing tourist mobility from Turkey to Greece. In the research, a dataset consisting of 20 highly-interactive YouTube videos selected as a sample from the universe of Greece travel videos, along with over 35,000 comments on these videos, was analyzed using a mixed-methods approach. Significant findings indicate that Turkish tourists' perception of Greece is positive due to reasons such as economic accessibility and service quality, but behind this trend lies a strong socio-economic reactivity towards the tourism approach in Turkey. The study argues that this tourism trend is not merely a simple holiday preference, but a symbolic escape in the form of a 'quest for an accessible and quality experience' that has developed as a reaction to the current conditions in Turkey.
Keywords: Sociology of Tourism; Sentiment Analysis; Social Media; Türkiye-Greece Tourism; Digital Word-of-Mouth Marketing